Potential of Trichoderma asperellum for biocontrol of Fusarium wilt in banana - Chaves, N.P.; Staver, Charles; Dita, M.A. (International Society for Horticultural Science, 2016)
A total of 72 fungal endophytes were isolated from surface-sterilized roots of healthy 'Gros Michel' (AAA genome, Gros Michel subgroup) banana plants in Turrialba, Costa Rica. In vitro and in vivo tests were carried out in order to identify microorganisms with potential activity against Fusarium oxysporum f. sp. cubense (Foc, race 1). In vitro tests revealed that 22 isolates inhibited the growth of Foc. The four most effective isolates were selected for suppression of Foc under greenhouse conditions. Plants treated with the four isolates showed a significant reduction of external and internal symptoms compared with untreated plants. Based on sequence analyses of specific genome regions [elongation factor - Tefa-1α or Internal Transcribed Spacer - ITS], the fungi tested in the greenhouse were identified as Trichoderma asperellum. Field trials are currently underway in Costa Rica to verify the performance of T. asperellum isolates as potential biological control agents against Foc. Results indicate that certain endophytic microorganisms may play important roles in controlling Fusarium wilt in banana. A better understanding of the antagonistic mechanisms displayed by endophytes in order to provide the best conditions to optimize the antagonistic activities of beneficial strains is still required.